Respuesta :
Answer:
Option C is correct
Multiply both sides of the equation by [tex]\frac{1}{2}[/tex]
Step-by-step explanation:
Given the equation:
[tex]2x^2+12x = 32[/tex]
Multiply both sides by [tex]\frac{1}{2}[/tex] we get;
[tex]\frac{1}{2} \cdot (2x^2+12x) = \frac{1}{2} \cdot 32[/tex]
Simplify:
[tex]x^2+6x = 16[/tex]
Subtract 16 from both sides we have;
[tex]x^2+6x-16=0[/tex]
Therefore, the first step to solve the equation by completing the square is,
Multiply both sides of the equation by [tex]\frac{1}{2}[/tex]